Keterkaitan Pertumbuhan Ekonomi dan Tingkat Pengangguran Di Provinsi Jambi Analisis Jangka Pendek dan Jangka Panjang - Fauzan Aldilah Putra; Yulmardi; Zulfanetti (JOURNAL OF SHARIA ECONOMICS, 2026)
This study aims to analyze the effect of economic growth, investment, government expenditure, and labor force on unemployment in Jambi Province, both in the short-run and the long-run, as well as to examine the existence of long-term equilibrium relationships and adjustment mechanisms among variables. The data used in this study are time series data for the period 1995–2024, analyzed using the Error Correction Model (ECM). The results show that in the long-run, economic growth and investment have a negative and significant effect on unemployment rate, while the labor force has a positive and significant effect. Meanwhile, government expenditure does not have a significant effect in the long-run. In the short-run, economic growth and investment do not have a significant effect on unemployment rate, whereas government expenditure has a negative and significant effect, and the labor force has a positive and significant effect on unemployment rate in Jambi Province. The cointegration test results indicate the existence of a long-term equilibrium relationship among variables in the model, and the negative and significant Error Correction Term (ECT) confirms the presence of an adjustment mechanism from short-term disequilibrium toward long-term equilibrium